Isolation and identification of Alternaria alstroemeriae causing postharvest black rot in citrus and its control using curcumin-loaded nanoliposomes - Li, Jie; Zhang, Zuyun; Yang, Ping; Zhao, Yu; Fang, Jiaxin; Yang, Tingting; Yang, Ruopeng (Frontiers in Microbiology, 2025)
Citrus black rot caused by the pathogen Alternaria alstroemeriae severely affects the growth and production of citrus industry. In order to further elucidate the pathogen of citrus fruit rot in Yunnan Province, the pathogenic fungi causing citrus fruit rot were identified through isolation and purification, pathogenicity testing, morphological characteristics, and rDNA ITS sequence analysis. Meanwhile, we synthesized curcumin-loaded nanoliposomes, a potential management approach to control citrus postharvest pathogen, and conducted vitro and vivo experiment to investigate the effects of different curcumin-loaded nanoliposomes treatments inhibitory effect to pathogen A. alstroemeriae. The results showed that the pathogenic fungi of citrus rot diseases were A. alstroemeriae, Rhizopus arrhizus, Aspergillus flavus and Penicillium digitatum. The curcumin-loaded nanoliposomes had inhibitory effect on A. alstroemeriae, in vitro experiment showed that the minimum fungicidal concentration (MIC) of curcumin-loaded nanoliposomes against the hyphae growth of A. alstroemeriae was 10 μmol/L, and 4MIC treatment significantly reduced the occurrence of black rot in citrus fruit in vivo test. Curcumin-loaded nanoliposomes also enhanced the activities of the enzymes PPO, APX, POD, PAL, GR and CAT of citrus, decreased the O2− production rate. The accumulation of ASA, GSH and hydrogen radical scavenging rate in Citrus reticulata Blanco ‘Orah’ were increased in the curcumin-loaded nanoliposomes treatment fruit, which may be directly responsible for the delayed onset of black rot disease. Furthermore, curcumin-loaded nanoliposomes treatment maintained the quality of citrus fruit by delaying the TSS, TA degradation and higher level of total phenolics and flavonoid contents in citrus fruit. Overall, our findings revealed that curcumin-loaded nanoliposomes, functioning as a plant elicitor, could effectively modulate physiological enzyme activities to confer the black rot resistance in citrus, which highlighted the potential of curcumin-loaded nanoliposomes for sustainable agricultural practices.